Towards a wireless sensing infrastructure for smart mobility. (May 2023) - Husain, Syed Faizan; Tutumluer, Erol; Mechitov, Kirill A.; Qamhia, Issam I.A.; Spencer, Bill; Riley Edwards, J.
Abstract: This paper presents a suite of wireless sensing solutions for the continuous monitoring of transportation infrastructure using traditional and emerging sensor technologies. First, various pavement sensing technologies are discussed followed by a suitability assessment survey to select suitable inter-sensor and gateway-to-cloud communication technologies for the sensors requiring lower and higher bandwidths. Selection recommendations were then made based on multi-disciplinary analyses of strengths, weaknesses, opportunities, and threats (SWOT) of various communication technologies and proposed wireless architectures for sensing infrastructure for smart mobility (SISM). Further, recommendations were made concerning the implementation of proposed wireless architectures for wireless and continuous monitoring of transportation infrastructure at the proposed Illinois Autonomous and Connected Track (I-ACT), which will be established at the University of Illinois Urbana-Champaign.